Reducing mortality from severe malaria in Sierra Leonean children by applying the World Health Organization's standard malarial protocol with additional sublingual glucose: A continuous quality improvement report. (July 2020) - Oxner, Asa; Vellanki, Meghana; Myers, Andrew; Bangura, Fonti; Bangura, Sheriff; Koroma, Augusta Mariama; Massaqoui, Rebecca; Gbao, Florence; Kamanda, Dora; Gassimu, Joseph; Kahn, Rebecca
Highlights: Adapting the WHO protocol for the treatment of severe malaria to a local context resulted in a marked reduction in mortality from severe malaria in pediatric cases Using a point-of-care decision support tool is a sustainable way to build capacity in nursing and pharmacy cadres in Sierra Leone Standardizing admissions, treatments, and communication among pediatric ward staff also created efficiency in the workday, which is a valuable benefit in settings with human resource constraints Abstract: Objectives: To reduce childhood mortality from severe malaria by implementing the World Health Organization's standardized malarial treatment protocol. Design: Observational study comparing the mortality rate from malaria before and after the intervention. Setting: Inpatient pediatric ward in a district referral hospital of Sierra Leone. Participants: A total of 1298 pediatric patients (ages 0-13 years, male and female) received the intervention, representing 100% of the pediatric patients admitted with severe malaria during the dates of implementation (there were no exclusion criteria). Interventions: We implemented the World Health Organization's standardized malarial protocol on September 30, 2015. Based on monthly run reports of mortality and root cause analysis, we adapted the malaria protocol by adding sublingual glucose as a treatment to target hypoglycemia complications in March 2016. Main Outcome Measures: The primary outcome was a change in monthly percent mortality from severe malaria, and the secondary outcome was the percent of mortality attributed to hypoglycemia. Results: The monthly average percent mortality from severe malaria dropped from 9% to 3.6% after the intervention, which was borderline statistically significant (p 0.06, CI 95% 1.5 to 5.6). The secondary outcome, percent of malarial deaths attributable to hypoglycemia via chart reviews, dropped from 83% to 44% across the study period. There was an increase in the average number of admissions for severe malaria from 71 to 153 children per month in the second half of the year (range from 49-212 per month). Conclusion: Implementing the WHO malaria treatment protocol with bedside tracking of protocol steps reduced malaria mortality and improved our ward's efficiency without adding any human or medical resources.